2020
DOI: 10.1123/jpah.2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sports Participation Associates With Cognitive Functioning and Academic Progression: An Analysis Using the Combined 2017–2018 National Survey of Children’s Health

Abstract: Background: The purpose of this study was to examine the independent and joint associations between physical activity (PA) and sports participation on academic performance variables within a representative sample of children and adolescents. Methods: Data were analyzed from the combined 2017–2018 National Survey of Children’s Health. Household addresses were randomly selected within each US state. One household parent answered health and wellness questions pertaining to one randomly selected household child (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
4
1
1
Order By: Relevance
“…Interestingly, our study also revealed that meeting the PA guidelines alone was not related to better AA. This research finding is inconsistent with prior research [43][44][45]. However, we further found that meeting combinations of either ST or sleep guidelines and PA guidelines was related to better AA.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our study also revealed that meeting the PA guidelines alone was not related to better AA. This research finding is inconsistent with prior research [43][44][45]. However, we further found that meeting combinations of either ST or sleep guidelines and PA guidelines was related to better AA.…”
Section: Discussioncontrasting
confidence: 99%
“…Behavioral covariates-Based on the previous studies ( 17 , 18 , 22 27 ), some selected behavioral factors were covariates of this study. Study participants answered an item that asked: “Over the last week, how many days did you spend on sports exercises for at least 60 minutes per day?”.…”
Section: Methodsmentioning
confidence: 99%
“…For example Burns et al ( 16 ) used data of a nationally representative sample that exhibited a positive dose-dependent relationship between participation in team sports and academic performance (self-reported A's and B's). In addition Burns et al ( 17 ) indicated that adolescents with sports participation were likely to report better academic performances. The cross-sectional evidence confirmed the positive roles of sports participation on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…El juego y la actividad física (AF) pueden producir mejoras en el rendimiento académico, ya que el alumnado que realiza AF y deporte regularmente durante la niñez presenta un 40-50% menos de probabilidad de tener dificultades para concentrarse, repetir curso y más opciones de retener lo estudiado y tomar decisiones (Burns et al, 2020). Pese a los beneficios asociados a la realización de AF, el volumen de tiempo extraescolar sedentario que el alumnado pasa, por ejemplo, delante de las pantallas es cada vez mayor (Valencia-Peris et al, 2016).…”
Section: Introductionunclassified